Download presentation

Presentation is loading. Please wait.

Published byBenedict Berry Modified over 8 years ago

1
1. Describe the end behavior of the graph y = 2x 5 – 3x 2 + 5. 2. Sketch a graph of 3 rd degree with a zero at -5 (multiplicity 2) and a zero at 0 (multiplicity 1). 1

2
Real Zeros of Polynomial Functions.

3
To solve, you factor the problem, each factor must be factored down to at most a quadratic. To solve, put each factor equal to zero. 3

4
1. 2x 5 + 24x = 14x 3 2x 5 – 14x 3 + 24x = 0 2x(x 4 – 7x 2 + 12) = 0 2x(x 2 – 3)(x 2 – 4) = 0 2x=0 x 2 –3=0 x 2 –4=0 x=0 x 2 =3 x 2 = 4 x=±√3 x = ±2 2. 2y 5 – 18y = 0 2y(y 4 – 9) = 0 2y(y 2 – 3)(y 2 + 3) = 0 2y=0 y 2 –3=0 y 2 +3=0 y=0 y 2 = 3 y 2 = –3 y=±√3 y=±i√3 4

5
Long Division Synthetic Division 5

6
Divide 3x 3 – 5x 2 + 10x – 3 by 3x + 1 3x + 1 ) 3x 3 – 5x 2 + 10x – 3 6 Algebra II x2x2 3x 3 + x 2 -6x 2 + 10x - 2x -6x 2 - 2x 12x - 3 + 4 12x + 4 -7 -7. 3x + 1 +

7
Divide 2x 3 – 7x 2 – 17x – 3 by 2x + 3 2x + 3 ) 2x 3 – 7x 2 – 17x – 3 7 x2x2 2x 3 + 3x 2 -10x 2 - 17x - 5x -10x 2 - 15x - 2x - 3 - 1 -2x - 3 0

8
Divide 6x 2 + x – 7 by 2x + 3 2x + 3 ) 6x 2 + x – 7 8 3x 6x 2 + 9x -8x- 7 - 4 - 8x - 12 5 5. 2x + 3 +

9
Divide 4x 3 + 5x 2 - 3x + 10 by x 2 + 3 x 2 + 0x + 3 ) 4x 3 + 5x 2 – 3x + 10 9 4x 4x 3 + 0x 2 + 12x 5x 2 – 15x + 10 + 5 5X 2 + 0x + 15 -15x – 5 x 2 + 3

10
Divide -3x 3 + 4x – 1 by x - 1 x - 1 ) -3x 3 + 0x 2 + 4x – 1 10 -3x 2 -3x 3 + 3x 2 -3x 2 + 4x - 3x -3x 2 + 3x 1x - 1 + 1 1x - 1 0

11
Divide a polynomial by a binomial The polynomial must be in standard form Be sure to add zeros when needed for missing placeholders The divisor must be a linear binomial with a leading coefficient of 1 and in the form x + k 11 Algebra II

12
12 Divide x 3 + 2x 2 – 3x - 6 by x + 2. X = -2 -2 1 2 - 3 -6 times 10 0 -3 6 Now solve x 2 – 3 = 0 to find the remaining zeros. -++ 2

13
13 Divide 6x 3 – 19x 2 + 16x - 4 by x - 2. X = 2 2 6 -19 16 -4 times 12 6-7 -14 2 4 0 Now solve 6x 2 – 7x + 2 = 0 +++

14
14

15
15

16
V = x 3 + 9x 2 – x – 105 Given sides: x – 3 and x + 5 16 Algebra II

17
Divide 6x 3 + 11x 2 – 12x – 13 by 3x + 1 using long division. Divide 10x 3 – 10x 2 – 2x + 4 by x + 3 using synthetic division. Factor 4x 3 – 3x 2 – 25x – 6 using synthetic division given that one zero is -2. Solve 6x 3 + 23x 2 – 33x + 10 given that one zero is -5. 17 Algebra II

Similar presentations

© 2024 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google